Dissaving In the Era of "Free" Care for Tuberculosis (TB): A Qualitative Exploration of Financial Coping and Enablers Among Patients with Co-Prevalent TB-HIV/ TB-Diabetes in Bhavnagar Region, Western India - Mihir Rupani; Sheetal Vyas (Medsci Publications, 2022)
Background: India reports the highest number of cases of tuberculosis (TB) in India. Patients with TB employ negative financial coping mechanisms (dissaving) to make up for the costs of care. Our objectives were to explore the dissaving employed and enablers perceived by patients with TB-HIV, patients with TB-diabetes, and program managers of TB. Methods: We conducted qualitative in-depth interviews among eight TB-HIV patients, eight TB-diabetes patients, and seventeen program managers of TB in the Bhavnagar region (western part of India). An interview guide focusing on the coping strategies and enablers was used. Interviews were audio-recorded, transcribed, and analyzed using thematic analysis (codes and categories). Results: Borrowing money, taking a loan on interest, selling jewellery, taking up employment by the spouse, and mortgaging assets were the negative financial coping strategies employed by patients with TB-HIV co-infection/ TB-diabetes comorbidity. Free diagnosis, free treatment, accessible health facilities, support from health workers, bi-directional screening, and collaborative integration were some of the enablers perceived by patients and program managers. Conclusions: Even in settings with a decentralized "free" model of TB care, patients with co-prevalent TB-HIV/ TB-diabetes employ dissaving to offset the costs of care. The cash transfer scheme for patients with TB should be realigned to meet the financial protection targets of zero catastrophic costs by the year 2030.